2018
DOI: 10.3390/mi9110586
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Simultaneous Determination of Paraquat and Creatinine in Human Serum Using a Piece of Paper

Abstract: Paraquat intoxication is characterized by acute kidney injury and multi-organ failure, causing substantial mortality and morbidity. This study aims to develop a 2-in-1 paper-based analytical device to detect the concentrations of paraquat and creatinine in human serum, which can help clinicians diagnose patients with paraquat poisoning in a more rapid and geographically unrestricted manner. The procedure involves fabrication of a paper-based analytical device, i.e., printing of design on a filter paper, heatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…PQ poisoning can result in multiple organ failure that primarily affects the lungs, kidneys, liver and nervous system. The kidneys, as the main detoxification organ, encounter very high concentrations of PQ during the body’s process of PQ elimination, thus leading to acute kidney injury [16]. Therefore, protecting kidney function is also an effective treatment for PQ poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…PQ poisoning can result in multiple organ failure that primarily affects the lungs, kidneys, liver and nervous system. The kidneys, as the main detoxification organ, encounter very high concentrations of PQ during the body’s process of PQ elimination, thus leading to acute kidney injury [16]. Therefore, protecting kidney function is also an effective treatment for PQ poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…We then loaded 8 µL of sample onto the test zone and allowed it to rest for 10 min at 25 • C. Detection results were recorded using a digital camera and the signal was analyzed using ImageJ software. The RGB color value of each detection result was obtained, and the R value was used for further calculation [13,36]. We subtracted original test zone background values for each detection result.…”
Section: Performing Origami-based Detection Of Paraquatmentioning
confidence: 99%
“…However, successful detection of multiple analytes using a single PAD relied on maintaining particular, sometimes critical, conditions such as moisture level. In a previous study, we showed that paraquat detection in a PAD required a wet environment [13,36]. Traditional ELISA, however, requires application of multiple reagents, and the time to complete such a process using paper increases the likelihood of any moisture-sensitive components drying out.…”
Section: O-pad For Paraquat Detectionmentioning
confidence: 99%
See 2 more Smart Citations